Quality of online media reporting of suicidal behaviour in Iran during the COVID-19 pandemic – in reference to World Health Organization guidelines. Issue 1 (2022) - Arafat, S.M. Yasir; Ahmad, Araz; Saeed, Ayoob; Feizi, Omar; Saeed, Fahimeh; Menon, Vikas; Kar, Sujita; Shoib, Sheikh
No abstract available